Posttranslational processing of a new class of hydroxyproline-containing proteins. Prolyl hydroxylation and C-terminal cleavage of tobacco (Nicotiana tabacum) vacuolar chitinase. - Sticher, L (1993)
The fungicidal class I chitinases (EC 3.2.1.14) are believed to be important in defending plants against microbial pathogens. The vacuolar isoforms of tobacco (Nicotiana tabacum), chitinases A and B, are the first examples of a new type of hydroxyproline-containing protein with intracellular location, enzymic activity, and a small number of hydroxyprolyl residues restricted to a single, short peptide sequence. We have investigated the posttranslational processing and intracellular transport of transgene-encoded chitinase A in callus cultures of Nicotiana tabacum L. cv Havana 425 and leaves of Nicotiana sylvestris Spegazzini and Comes. Pulse-chase experiments and cell fractionation show that chitinase A is processed in two distinct steps. In the first step, the nascent protein undergoes an increase in apparent M(r) of approximately 1500 detected by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. Experiments with the inhibitor of prolyl hydroxylation, alpha,alpha'-dipyridyl, and pulse-chase labeling of cells expressing recombinant forms of chitinase A indicate that the anomalous increase in M(r) is due to hydroxylation of prolyl residues. This step occurs in the endomembrane system before sorting for secretion and vacuolar transport and does not appear to be required for correct targeting of chitinase A to the vacuole. The second step is a proteolytic cleavage. Sequencing of tryptic peptides of the mature proteins indicates that during processing essentially all molecules of chitinase A and B lose a C-terminal heptapeptide, which has been shown to be a vacuolar targeting signal. This appears to occur primarily in the endomembrane system late in intracellular transport. A model for the posttranslational modification of chitinase A is proposed.